Prevalence of depression and its associated factors among Malay male methadone maintenance therapy patients - Md Aris, Mohd Aznan; Tin, Myo Han; Abdullah, Fa’iza; mohd khanafiah, Muhammad Farisham; Muhamad Fauzi, Muhammad Syahir; Mohamad, Ramzi Akram (2015)

(untitled)
Depression is one of the most common psychiatric conditions among men with methadone maintenance therapy (MMT) in Malaysia. Poor psycho-social functioning and risk of relapse to heroin use among MMT patients could be predicted based on their depression level. The doctors should know depression status of MMT patients to reduce the impact of depression on the individual and compliance to MMT.